Role of Cytokinin, Strigolactone, and Auxin Export on Outgrowth of Axillary Buds in Apple - Tan, Ming; Li, Guofang; Chen, Xilong; Xing, Libo; Ma, Juanjuan; Zhang, Dong; Ge, HongJuan; Han, Mingyu; Sha, Guangli; An, Na (Frontiers in Plant Science, 2019)
Shoot branching is regulated by phytohormones, including cytokinin (CK), strigolactone (SL) and auxin in axillary buds. The correlative importance of these phytohormones in the outgrowth of apple axillary buds remains unclear. In this study, the outgrowth dynamics of axillary buds of a more-branching mutant (MB) and its wild-type (WT) of Malus spectabilis were assessed using exogenous chemical treatments, transcriptome analysis, paraffin section, and reverse transcription-quantitative PCR analysis (RT-qPCR). High contents of CK and abscisic acid coincided in MB axillary buds. Exogenous CK promoted axillary bud outgrowth in the WT but not in MB, whereas exogenous gibberellic had no significant effect on bud outgrowth in the WT. Functional analysis of transcriptome data and RT-qPCR analysis of gene transcripts revealed that MB branching were associated with CK signaling, auxin transport, and SL signaling. Transcription of the SL-related genes MsMAX1, MsD14, and MsMAX2 in the axillary buds of MB was generally upregulated during bud outgrowth, whereas MsBRC1/2 were generally downregulated both in WT and MB. Exogenous SL inhibited outgrowth of axillary buds in the WT and the apple varieties T337, M26, and Nagafu 2, whereas axillary buds of the MB were insensitive to SL treatment. Treatment with N-1-naphthylphalamic acid (NPA; an auxin transport inhibitor) inhibited bud outgrowth in plants of the WT and MB. The transcript abundance of MsPIN1 was generally decreased in response to NPA and SL treatments, and increased in CK and decapitation treatments, whereas no consistent pattern was observed for MsD14 and MsMAX2. Collectively, the present results suggest that in apple auxin transport from the axillary bud to the stem may be essential for the outgrowth of axillary buds, and at least, is involved in the process of bud outgrowth.